Generalized Propensity Score Matching with Multilevel Treatment Options - Onur Baser (Journal of Health Economics and Outcomes Research)
**Background:** Although conventional form of propensity score matching (PSM) is widely used in outcomes research field, its application on multilevel treatment is limited.